Analysis of Simple Mechanism Using MSC Adams - Delyová, Ingrid; Hroncová, Darina; Frankovský, Peter (Manufacturing Technology Journal, 2014)
In addressing the motion of machine parts, machines and equipment it is necessary to first create a kinematic model. Kinematic model of a device schematically captures all its properties which are essential in kinematic analysis. This article deals with kinematic analysis of a simple mechanism executing a rotational movement. We analyzed the movement of its end points. Numerical solution was implemented by classical kinematics using different coordinate systems, while model mechanism has been also modeled and solved in the program MSC Adams. The result of the computer simulation is designation of the searched kinematic parameters and the other required parameters of the solved model. Solutions are time kinematic variables over time, which are shown graphically.
Keywords: Kinematics; Analytical solution; Numerical solution; Simulation